A survey of computational methods for pricing Asian options - Nieuwveldt, Fernando Damian (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Mathematical Sciences. Applied Mathematics))--University of Stellenbosch, 2009.